2017
DOI: 10.1111/apt.14256
|View full text |Cite
|
Sign up to set email alerts
|

Is early recurrence of hepatocellular carcinoma in HCV cirrhotic patients affected by treatment with direct‐acting antivirals? A prospective multicentre study

Abstract: Probability of HCC early recurrence in patients who had HCC previously cured remains high, despite HCV eradication by DAAs. Risk was comparable but not higher to that reported in literature in DAA-untreated patients. Previous HCC recurrence and tumour size can be used to stratify the risk of HCC early recurrence. Further studies are needed to assess impact of DAAs on late recurrence and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
129
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(149 citation statements)
references
References 23 publications
(56 reference statements)
17
129
3
Order By: Relevance
“…HCC recurred in seven patients (2.2%). Other recently published studies did not find any increased risk of recurrent HCC with DAA . In a metaanalysis including 17 studies (2352 patients) on HCC recurrence following DAA therapy in patients with chronic HCV who received curative HCC treatment (IFN = 7, DAA = 10; prospective = 11, retrospective = 5, retrospective‐prospective = 1), DAA therapy was not associated with higher rate of HCC recurrence (RR 0.62; 95% CI 0.11‐3.45, P = .56) .…”
Section: Daa and The Risk Of Hccmentioning
confidence: 83%
See 1 more Smart Citation
“…HCC recurred in seven patients (2.2%). Other recently published studies did not find any increased risk of recurrent HCC with DAA . In a metaanalysis including 17 studies (2352 patients) on HCC recurrence following DAA therapy in patients with chronic HCV who received curative HCC treatment (IFN = 7, DAA = 10; prospective = 11, retrospective = 5, retrospective‐prospective = 1), DAA therapy was not associated with higher rate of HCC recurrence (RR 0.62; 95% CI 0.11‐3.45, P = .56) .…”
Section: Daa and The Risk Of Hccmentioning
confidence: 83%
“…There are no recommendations for adjuvant therapies in clinical practice guidelines . Data are also limited on DAA regimens (Table ) …”
Section: Daa and The Risk Of Hccmentioning
confidence: 99%
“…Population studies identified HCC risk factors in patients who have achieved SVR as genotype 3, advanced fibrosis, diabetes, male gender and age . A prospective multicenter study by Cabibbo et al observed that HCV‐HCC patients successfully HCC treatment via chemoembolization, ablation, or resection who were subsequently treated with DAAs and achieved SVR had 6‐, 12‐ and 18‐month HCC recurrence rates of 12%, 26.6% and 29.1%, respectively. Therefore, while the total number of patients with HCV listed for transplant is decreasing, we are not observing the same magnitude of effect on the HCV‐HCC population on the transplant list due to HCC still being a prevalent morbidity in HCV patients in spite of achieving SVR.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective multicenter study by Cabibbo et al, (58) and a retrospective cohort by Huang et al, (56) also showed the risk of HCC recurrence was not higher than that of observed in DAA -unexposed patients. Ikeda et al, even suggested that DAA therapy significantly decreased recurrence rate after adjustment with covariates of tumor multiplicity, alpha -fetoprotein (AFP) value, and prothrombin time on the basis of a multivariate analysis (59).…”
Section: "Hcc Recurrence" In Daa -Treated Patientsmentioning
confidence: 88%